2021
DOI: 10.1155/2021/8854025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment on Detection of 37 Pesticide Residues in Chrysanthemum indicum

Abstract: This study aimed to develop a method, followed by gas chromatography-mass spectrometry, for detecting 37 pesticides in Chrysanthemum indicum (C. indicum) and investigating the decrease in the matrix-induced enhancement effect. The influence of QuEChERS extraction and matrix solid-phase dispersion (MSPD) on the recovery and matrix effect (ME) was compared. extraction and matrix solid-phase dispersion (MSPD) on the recovery and matrix effect (ME) was compared to decrease the ME. The cleanup sorbents, volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…It is hypothesized that some particular components in tea substrates could suppress the OH-T-CA signal intensity in ESI − mode, in spite of a purification step. This was in line with other researchers' findings, which reported that the majority of pesticides had matrix suppression effects [36,37]. As a result, a series of matrix-matched standards were utilized for quantification in the current study.…”
Section: Linear Matrix Effects and Limit Of Detectionsupporting
confidence: 88%
“…It is hypothesized that some particular components in tea substrates could suppress the OH-T-CA signal intensity in ESI − mode, in spite of a purification step. This was in line with other researchers' findings, which reported that the majority of pesticides had matrix suppression effects [36,37]. As a result, a series of matrix-matched standards were utilized for quantification in the current study.…”
Section: Linear Matrix Effects and Limit Of Detectionsupporting
confidence: 88%
“…In particular, in the case of herbal decoctions, since patients take them within approximately 24 h after dispensing, test results should be obtained as quickly as possible [10]. However, various types of herbal medicines are used according to the prescriptions, and the procedure to analyze pesticide residues in the Korean Pharmacopoeia is so complicated that it takes approximately 2-7 days to determine the results [11]. Therefore, developing an effective analysis method that can shorten the test time and increase the accuracy is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of high-resolution mass spectrometry (HRMS) in resolution and obtaining appropriate selectivity by improving mass resolution provides new opportunities for residue analysis. Initially, GC and Q-TOF instruments were coupled through the atmospheric pressure chemical ionization (APCI) interface to achieve this goal [ 16 18 ], but recently, a special GC and electron ionization (EI) Orbitrap MS system was introduced. The system combines the peak capacity and chromatographic resolution of gas chromatography with the sub-ppm mass accuracy of the Orbitrap system to provide higher resolution (15,000, 30,000, 60,000, and 120,000 at half-maximum (FWHM) at m / z 200).…”
Section: Introductionmentioning
confidence: 99%